2019
DOI: 10.1155/2019/4568964
|View full text |Cite
|
Sign up to set email alerts
|

Natural Sesquiterpene Lactones Enhance Chemosensitivity of Tumor Cells through Redox Regulation of STAT3 Signaling

Abstract: STAT3 is a nuclear transcription factor that regulates genes involved in cell cycle, cell survival, and immune response. Although STAT3 activation drives cells to physiological response, its deregulation is often associated with the development and progression of many solid and hematological tumors as well as with drug resistance. STAT3 is a redox-sensitive protein, and its activation state is related to intracellular GSH levels. Under oxidative conditions, STAT3 activity is regulated by S-glutathionylation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 153 publications
(124 reference statements)
1
17
0
Order By: Relevance
“…14,15 Several natural sesquiterpene lactones, such as alantolactone, parthenolide, and dehydrocostuslactone, exhibit anti-TNBC effects via downregulation of p-STAT3 expression. 25 In our study, we found that BA inhibited the expression of STAT3 in MDA-MB-231 and MDA-MB-468 cells, indicating another potential route for the anti-TNBC activity of BA.…”
Section: Ba Inhibited Cancer Cell Proliferation In Vivosupporting
confidence: 52%
“…14,15 Several natural sesquiterpene lactones, such as alantolactone, parthenolide, and dehydrocostuslactone, exhibit anti-TNBC effects via downregulation of p-STAT3 expression. 25 In our study, we found that BA inhibited the expression of STAT3 in MDA-MB-231 and MDA-MB-468 cells, indicating another potential route for the anti-TNBC activity of BA.…”
Section: Ba Inhibited Cancer Cell Proliferation In Vivosupporting
confidence: 52%
“…GSH levels associate with chemosensitivity and programmed cell death of tumor cells. 12,13 However, the content and the effect of GSH in EOC have not been fully researched.…”
Section: Introductionmentioning
confidence: 99%
“…Xanthium fruit extracts contain various natural compounds including xanthanolides (Chen et al, 2013; Jiang et al, 2017; Vasas & Hohmann, 2011; Wang et al, 2013). Among them, we were interested in xanthanolides because they are already known to suppress the proliferation of cancer cells through multiple mechanisms, including the suppression of telomerase activity, inhibition of STAT3 activation, and promotion of apoptosis (Butturini, Carcereri de Prati, Boriero, & Mariotto, 2019; Fang et al, 2018; Vasas & Hohmann, 2011). UPLC‐PDA‐QTof‐MS analyses were carried out on a Micromass QTof Premier™ instrument equipped with an ACQUITY BEHC 18 chromatography column.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the EA fraction of the Xanthium fruit extracts decreased the proliferation of the DU145 cancer cells in a time-and concentration-dependent manner(Figure 1b).These results implied that Xanthium fruit extracts contain STAT3 inhibitory compounds.3.2 | Isolation of the STAT3 inhibitory compound EXT from the Xanthium fruit extractsXanthium fruit extracts contain various natural compounds includingxanthanolides(Chen et al, 2013;Jiang et al, 2017;Vasas & Hohmann, 2011;Wang et al, 2013). Among them, we were interested in xanthanolides because they are already known to suppress the proliferation of cancer cells through multiple mechanisms, including the suppression of telomerase activity, inhibition of STAT3 activation, and promotion of apoptosis(Butturini, Carcereri de Prati, Boriero, & Mariotto, 2019;Fang et al, 2018;Vasas & Hohmann, 2011). UPLC-PDA-QTof-MS analyses were carried out on a Micromass QTof Pre-mier™ instrument equipped with an ACQUITY BEHC 18 chromatography column.…”
mentioning
confidence: 99%